Differences of patients with Angle class I type 1 profile before and after treated with removable orthodontic appliance - Nada, Novita Asti; Zenab, N.R.Yuliawati; Malik, Isnaniah (Padjadjaran Journal of Dentistry, 2017)
ABSTRACTIntroduction: Children with bad habit and the persistence of deciduous teeth can caused malposition of anterior permanent teeth or Angle Class I Type 1 malocclusion. One of the curative treatment is removable orthodontic appliance. The purpose of this study was to determine the difference of dental arch width, overjet and overbite in patients with Angle Class I Type 1 before and after treated with removable orthodontic appliance in Dental Student Clinic in Faculty of Dentistry Padjadjaran University. Method: The research was conducted using 33 patient study models of Angle Class I Type 1 who were treated with removable appliance from year 2014 to 2015 in accordance with the criteria. Research method statistically analyzed with paired t-test sample. The dental arch width, overjet and overbite were measured with caliper of patient study models before and after treatment with removable orthodontic appliance. Results: The difference value before and after treatment using removable orthodontic appliance were 2.8% for anterior dental arch width, 2.4% for posterior dental arch width, 10.7% for overjet and 11% for overbite. Conclusion: The differences value of dental arch width, overjet and overbite in patients with Angle Class I Type 1 before and after treated with removable orthodontic appliance showed only a little progress of the treatment caused by multiple factors. Keywords: Angle class I type 1, Dental arch width, Overjet, Overbite